Pay-out Phase for The Universal Pension Funds in Bulgaria – New Risks and Opportunities for the Insured Individuals - Milev, Jeko (UNWE Yearbook, 2021)
The universal pension funds in Bulgaria are going to enter a new phase in 2021. Women born at the beginning of 1960 are going to receive part of their pension benefit from the universal pension fund of their choice. The so-called pay-out phase is knocking on the door which means that some new risks and opportunities arise for the insured individuals born after 31.12.1959. The article examines the proposed changes in the normative rules concerning the pay-out phase for the universal pension funds and analyses some of the risks that currently appear on the surface. There is a clear need for some additional reforms in the supplementary compulsory pension insurance in Bulgaria if policymakers really want fully funded private pension schemes to support the financially constrained pay-as-you-go column of the social security system in the long term. The article suggests some measures that would be beneficial both for the insured individuals and for the pension system in Bulgaria.